Advancement of stannite Cu2CoSnS4 thin films deposited by sol gel dip-coating route. (1st June 2022) - Ziti, Ahmed; Hartiti, Bouchaib; Smairi, Salma; Labrim, Hicham; NOURI, Youssef; Belafhaili, Amine; Nkuissi, Hervé Joël Tchognia; Fadili, Salah; Tahri, Mounia; Thevenin, Philippe
Abstract: In this research effort, we synthesized copper-cobalt-tin-sulphur Cu2 CoSnS4 (CCoTS) absorbers by sol–gel process associated with the dip-coating deposition technique on the ordinary glass substrates. We synthesized the impact of annealing temperature without utilization sulfurization on the structural, compositional, morphological, optical and electrical characteristics of layers annealed at 280 °C, 300 °C, 320 °C and 340 °C. CCoTS absorbers have been controlled by different control techniques included x-ray diffraction (XRD), Raman spectroscopic, Energy dispersive x-ray spectroscopy (EDS), Scanning electron microscopy (SEM), UV–vis spectroscopy and four-point probe technique (FPP). XRD patterns exhibited a polycrystalline structure with peaks agreeing to the (112), (204) and (312) directions and matching well with those of the pure stannite phase of CCoTS. The size of crystallites was found in the variety of 8.23–11.27 nm. Raman spectroscopic presented a peak at 332 cm −1 which is the signature of the pure stannite phase of CCoTS. EDS analysis measurements presented a close stoichiometric CCoTS thin films composition. SEM micrographs demonstrated an enhancement in films density and uniformity with annealing temperature rises. It was found that the band gap decreased from 1.72 to 1.5 eV with rising of annealing temperature. The sheet resistance was observed between 27.83 and 56.23 Ω sq −1 . These properties are quite interesting and can make the dip-coater CCoTS films as suitable novel absorbers for photovoltaic devices.